MY SAY: The new champions - Abd Razak, Dzulkifli (2009)
China proudly commemorated 60 years of Communist Party rule last week with what seemed to be the largest celebration the country had ever witnessed. To use a phrase coined during the recent World Economic Forum in Dalian, China has pointedly distinguished itself as one of the "new champions" of the day. Maybe, as also mentioned during the forum, this is because the republic recognised the fact that "the teachers have made big mistakes" — referring to the West's chief role in the global financial and economic fiasco — leaving it with the clear option to lead.